Database design of the Malaysia public figures web archive repository: a social and cultural heritage web collections - Farrah Diana Saiful Bahry; Noraizan Amran; Tesa Eranti Putri; Ramli, Muhammad Idzwan (Collection building, 2022)
Purpose>The growth of web emerging technology and data visual demand from the World Wide Web (WWW) makes the need for information repositories become vital. Proper database development will assure the repository managing web content effectively aligns with web archive metadata standards. This paper aims to present the database design process for web archive content repository specifically to maintain social and cultural heritage values upon Malaysians as Mfigures.Design/methodology/approach>The empirical process start with literature review and validation from expert on the elements and scopes of research. Then, structured database design guideline which part of database life cycle (DBLC) was applied and combined with the step of comparative and mapping the conceptual model with metadata standard that is relevant with web archive content. The paper focuses on the first three stages: Database Initial Study, web archiving and Metadata standard mapping; and conceptual design to focus on data modelling. Another two stages of database design are logical design and physical design will be exposed later.Findings>The empirical process has produced initial conceptual data model, database structure that can be a basis of web archiving repository. The data model had also been verified with metadata data standards to assure the database structure implementation cater the need of web archiving repository features especially web information discovery.Research limitations/implications>Nevertheless, database design is the most effective way to develop good information architecture on the Net, but the absence of some important fields on related tables have been identified such as subject, language, coverage, right, publisher and contributor. The MFigures’ database schema will continuously improve for better scope and coverage of web archive content suite with future information demands on the WWW.Practical implications>The conceptual data model act as a communication tool by the technical team in web application development. It can be revisited to suite with other different database management system or to suite with other similar scope of information repository requirements.Social implications>Mfigures was uniquely designed for collecting Malaysian social and cultural heritage, which are rarely design before, and it can be beneficial as Malaysia society future references for excellent motivations roles and successful stories.Originality/value>The Mfigure conceptual data model was empirically design and gone through a proper validation process by the industrial and academic experts.